Perencanaan Pembangkit Listrik Tenaga Hibrid (PV dan Mikrohidro) Terhubung Grid (Studi Kasus Desa Merden, Kecamatan Padureso, Kebumen) - Ana Nur Azizah; Sugeng Purbawanto (Departemen Teknik Elektro dan Informatika Sekolah Vokasi UGM, 2021)
Hybrid Power Plant is an integration of two or more power plants based on renewable energy or not. Indonesia targets 23% of new renewable energy in the national energy mix in 2025, Merden Village is one of the areas located in Padureso District, Kebumen Regency., which has a renewable energy-based power plant, namely PLTMH with a capacity of 2x200 kVa connected to the grid (PLN). However, from August to December it did not run optimally due to a lack of water supply from the Wadaslintang Reservoir. Based on the database form NASA, the village of Merden is an area that has radiation of 4,60 kWh/m2/day, with a high enough intensity, this village has the potential to be paired with photovoltaics as additional energy. This research uses the help of HOMER software with the parameters entered, among others, energy source (solar radiation intensity and water discharge), equipment specifications, cost and daily load profile. The results of this study are the electrical energy production of the two generators is 1.301.169 kWh per year with a total NPC value of -941.597 and an LCOE of - 0,056. The most optimal configuration is Microhydro 385 kW, PV 15kW, Battery 40 units, Bi-Directional Inverter 75 kW. This shows the additional of PV can be a reference because it can produce electrical energy for one full year.Keywords : Hybrid, Microhydro, PV, Grid, HOMER